Race, gender, sexuality, and the politics of the American judiciary - Hernandez, Samantha L.; Navarro, Sharon Ann (Cambridge University Press, 2019)
Machine generated contents note: Qualification, selection, and retirement characteristics of women, minorities, and minority women state Supreme Court judges / Nancy Bays Arrington -- Latinas and the Texas judiciary: the intersection of race, gender, and judiciary / Sharon A. Navarro -- Structural and partisan influences on the ascension of women of color to state appellate courts / Barbara L. Graham and Adriano Udani -- LGBT judges in the US / Donald Haider-Markel and Patrick Gauding -- Race, gender, and the battle to seat Constance Baker Motley, the first black woman appoint to the federal bench / Taneisha Nicole Means -- Diversity abound: will federal judicial appointees mirror a changing citizenry? / Shenita Brazelton and LaTasha Chaffin -- Marked for excellence: race, gender, and the treatment of Supreme Court-worthy nominees to the US Courts of Appeals / Lisa M. Holmes -- Navigating rising to the top: Justice Sotomayor / Samantha L. Hernandez